Building community health from the ground up: community gardens and food insecurity in North Carolina - Hafner, Robert (Kansas State University, 2019)
Community gardens are a potential option to help alleviate food security problems. This research evaluated North Carolina community garden cases that are in operation within counties where food security is a significant problem. The research sought to understand if North Carolina community garden projects help to alleviate food security issues; and if so, how. A case study of three different community gardens and their participants was conducted in order to answer this question. In reviewing each of the garden cases, it is apparent that each increases food security through its own unique garden framework. It is also apparent that different models for community engagement have a relationship with positive food security outcomes as well as positive outcomes for community growth within the context of the community garden. The research also points to how different models for governance, location, and success management practices may be useful in increasing positive food security outcomes. Further study is required in order to understand the degree to which the framework of each garden impacts food insecurity and how that may be leveraged for further successes in community development.
Keywords: Community Development; Food Security; Community Garden